1988
DOI: 10.1111/j.1751-1097.1988.tb02767.x
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Modes of Photodynamic Action by Cercosporin

Abstract: Abstract— Cercosporin, one of a number of 4,9‐dihydroxyperylene‐3,10‐quinones synthesized by plant pathogenic fungi, abundantly produces singlet oxygen when illuminated in solution. Singlet oxygen production is substantially decreased and superoxide production is greatly enhanced in the presence of the reducing agents ergothioneine (2‐thiol‐L‐histidine betaine) or urate. Both ergothioneine and urate enhance superoxide production at a rate approximately 25‐fold that elicited by an equimolar amount of methionine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
1
2

Year Published

1989
1989
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(31 citation statements)
references
References 27 publications
1
27
1
2
Order By: Relevance
“…In contrast, Paul and Snyder (2010) showed that a pre-treatment of EGT protected HeLa cells from growth-suppression and apoptosis of the superoxide producer pyrogallol. However, in in vitro studies, EGT did not quench superoxide (Dubost et al, 2007;Hartman et al, 1988). Indeed, Hartman et al (1988) demonstrated that when EGT instead of methionine was added as a reducing agent, superoxide formation was increased approximately 25-fold.…”
Section: Ergothioneine Is An Antioxidant Against Peroxide In Conidia mentioning
confidence: 94%
See 1 more Smart Citation
“…In contrast, Paul and Snyder (2010) showed that a pre-treatment of EGT protected HeLa cells from growth-suppression and apoptosis of the superoxide producer pyrogallol. However, in in vitro studies, EGT did not quench superoxide (Dubost et al, 2007;Hartman et al, 1988). Indeed, Hartman et al (1988) demonstrated that when EGT instead of methionine was added as a reducing agent, superoxide formation was increased approximately 25-fold.…”
Section: Ergothioneine Is An Antioxidant Against Peroxide In Conidia mentioning
confidence: 94%
“…However, in in vitro studies, EGT did not quench superoxide (Dubost et al, 2007;Hartman et al, 1988). Indeed, Hartman et al (1988) demonstrated that when EGT instead of methionine was added as a reducing agent, superoxide formation was increased approximately 25-fold.…”
Section: Ergothioneine Is An Antioxidant Against Peroxide In Conidia mentioning
confidence: 94%
“…Ergothioneine also interacts with ROS, most probably through the quenching of singlet oxygen (Hartman et al, 1988). In addition, the compound reacts with hydroxyl radicals (Rougee et al, 1988;Akanmu et al, 1991), and scavenges hypochlorous acid (Akanmu et al, 1991), peroxyl radical (Asmus et al, 1996), and peroxynitrite (Aruoma et al, 1997).…”
Section: Ergothioneine Protects Endothelial Cellsmentioning
confidence: 99%
“…Cercosporin, produced by several species of Cercospora, and isocercosporin, produced by Scolecotrichum graminis (agent of leaf streak in orchard grass [Dactylis glomerata L]) (Tabuchi et al, 1991), are photodynamic compounds. In the presence of sunlight and molecular oxygen they produce singlet oxygen (Hartman et al, 1988). Other photodynamic compounds, such as hypericin (a plant product) (Knox and Dodge, 1985), have been suggested as herbicides; however such compounds may be of high risk since they are toxic to life forms existing in sunlight and oxygen.…”
Section: Other Fungal Phytotoxinsmentioning
confidence: 99%